On the Demographic Adjustment of Unemployment - Barnichon, Regis; Mesters, Geert (The Review of Economics and Statistics, 2018)
The unemployment rate is one of the most important business cycle indicators, but its interpretation can be difficult because slow changes in the demographic composition of the labor force affect the level of unemployment and make comparisons across business cycles difficult. To purge the unemployment rate from demographic factors, labor force shares are routinely used to control for compositional changes. This paper shows that this approach is ill defined, because the labor force share of a demographic group is mechanically linked to that group's unemployment rate, as both variables are driven by the same underlying worker flows. We propose a new demographic-adjustment procedure that uses a dynamic factor model for the worker flows to separate aggregate labor market forces and demographic-specific trends. Using the U.S. labor market as an illustration, our demographic-adjusted unemployment rate indicates that the 2008–2009 recession was much more severe and generated substantially more slack than the early 1980s recession.